Cultural Adaptation of Skills Training in Affective and Interpersonal Regulation Therapy for Spanish-speaking Caribbean Veterans at the VA Caribbean Healthcare System: A preliminary study of feasibility and acceptability in a Primary Care setting - Rivera-Rivera, Naiomi; Calaf, Myralys; Pérez-Pedrogo, Coralee; Sánchez-Cardona, Israel; Villegas-Adorno, Yelitza (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2024)
The U.S. Department of Veterans Affairs has endorsed the Skills Training in Affective and Interpersonal Regulation (STAIR) therapy as an effective intervention for reducing PTSD symptoms, enhancing self-regulation, and improving interpersonal efficacy. However, Spanish-speaking veterans at the VA Caribbean Healthcare System lacked access to STAIR manuals in their preferred language. This study addressed this gap by translating and culturally adapting the STAIR therapy participant manual using the Ecological Validity Model (EVM). The materials were then tested in a randomized intervention with six Caribbean Spanish-speaking male veterans, aged 23-62, diagnosed with PTSD who received mental health services at the Primary Care Mental Health Integration (PC-MHI) level of care. Nonparametric tests were used to evaluate symptom progression, and content analysis was conducted on semi-structured interviews. There were no statistically significant changes in PTSD, emotion regulation, or interpersonal problems within the groups. However, participants in the intervention group reported clinically significant changes regarding PTSD symptoms. Interviews with therapists and STAIR participants highlighted improvements in social engagement and interpersonal boundaries. The intervention was found to be feasible and acceptable at PC-MHI. The culturally adapted Spanish version of the STAIR manual proved to be effective, suggesting that STAIR may be a viable approach for reducing PTSD symptoms and improving interpersonal and self-regulation strategies among Spanish-speaking veterans in primary care settings. A randomized control trial is recommended to further explore its efficacy.